Learning Media Development of Electronic Comic Based in Grade IV IPAS Major to Increase Students' Interest in Learning - Octavianto, Albert Ferdy; Astuti, Suhandi (ARKA INSTITUTE, 2022)
The development of electronic comic media aims to increase students' interest in learning science material in class IV. This R&D research was carried out using the ASSURE model. Based on the results of the validation test by material experts, a score of 66 was obtained, which, when presented, was 88%. Then, based on the results of validation by media experts, a score of 92 was obtained, which, when presented, was 92%. Meanwhile, the validation of learning experts obtained a score of 115, which, when presented, became 92%, where the score indicated a very good category and was feasible to use. Based on the results of the analysis of the different tests using the independent sample test technique, the calculated t value is 8.749 with sig. (2-tailed) 0.000, sig. 0.183, and a df of 74. Probability value 0.05, then H0 is rejected and Ha is accepted, so it can be said that the posttest results are higher than the pretest. Based on the results of the student-teacher questionnaire, respondents obtained results of 94% and 97%. From the data obtained, it can be said that comic media is effective in increasing students' interest in learning.